1988
DOI: 10.1093/jac/22.supplement_d.227
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and tolerance of fleroxacin in patients with urethritis caused by Chlamydia trachomatis

Abstract: In an open study, 22 patients with genito-urinary infection by Chlamydia trachomatis were treated with oral fleroxacin in varying dosage. Symptoms were relieved and cultures became negative in 19 patients, with three patients not assessable. Adverse reactions, affecting the central nervous system, the gastrointestinal tract and the skin (photosensitivity), were reported in seven patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Interestingly, despite the observation that Chlamydia trachomatis is more susceptible than U. urealyticum to fluoroquinolones in vitro, a higher fraction of patients with nongonococcal urethritis caused by U. urealyticum was cured by norfloxacin (75) and ciprofloxacin (235) than those with Chlamydia trachomatis, and ciprofloxacin appeared to be more effective (P = 0.12) than doxycycline (235). In contrast, ofloxacin (200 mg twice daily) (50, 243,530,622) or fleroxacin (400 to 800 mg per day) (603) given for 5 to 15 days eradicated Chlamydia trachomatis from the urethra or cervix in >90% of patients, a result comparable to that with doxycycline in one study (243). Urethritis that was culture negative for chlamydia responded to ofloxacin less well in men (530).…”
Section: Sexually Transmitted Diseasesmentioning
confidence: 94%
“…Interestingly, despite the observation that Chlamydia trachomatis is more susceptible than U. urealyticum to fluoroquinolones in vitro, a higher fraction of patients with nongonococcal urethritis caused by U. urealyticum was cured by norfloxacin (75) and ciprofloxacin (235) than those with Chlamydia trachomatis, and ciprofloxacin appeared to be more effective (P = 0.12) than doxycycline (235). In contrast, ofloxacin (200 mg twice daily) (50, 243,530,622) or fleroxacin (400 to 800 mg per day) (603) given for 5 to 15 days eradicated Chlamydia trachomatis from the urethra or cervix in >90% of patients, a result comparable to that with doxycycline in one study (243). Urethritis that was culture negative for chlamydia responded to ofloxacin less well in men (530).…”
Section: Sexually Transmitted Diseasesmentioning
confidence: 94%
“…Animal studies have suggested that there is excellent penetration of drug into most tissues (5, 18, 30-34, 41, 49, 53), but only limited information on tissue penetration of fleroxacin in humans is available (22,26,41,44,53). Initial clinical experience in the treatment of sexually transmitted diseases, urinary tract infection, skin and soft tissue infections, gastrointestinal infection, and even acute exacerbations of chronic bronchitis has been quite promising, with 74 to 100% bacteriological cure rates and a tolerability comparable to those for other drugs of this class (3,12,27,35,38,42,43,45,47). However, to optimize the clinical use of * Corresponding author.…”
mentioning
confidence: 99%
“…The fact that PET measurements yield only total concentrations of drug per gram of tissue and cannot differentiate between intra-and extracel- VOL. 40,1996 PHARMACOKINETICS OF [ 18 F]FLEROXACIN lular drug somewhat limits the conclusions that can be drawn. However, rough relationships between total tissue concentrations and MICs are suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Fleroxacin is a new fluoroquinolone that has been shown to possess a number of desirable characteristics: excellent bioavailability after oral administration, high concentrations in plasma relative to the susceptibilities of relevant pathogens, a long elimination half-life which is consistent with a once-a-day administration schedule, and good tissue penetration (2, 3, 5-9, 11, 19-23, 25-30, 32, 35-39, 43-50). In addition, the initial clinical experience with fleroxacin in the treatment of sexually transmitted diseases, urinary tract infection, skin and soft tissue infection, gastrointestinal infection, and acute bacterial exacerbations of chronic bronchitis has been encouraging (4,10,24,33,34,37,39,40,42).…”
mentioning
confidence: 99%